Dialog w metodzie indywidualnych przypadków - Karpińska-Szaj, Katarzyna (Neofilolog, 2010)
An individual case study is a research procedure and at the same time a practical approach which makes it possible to apply a variety of data gathering instruments. One such instrument is dialogue, which is described in this article as a tool meant for the diagnosis and treatment of difficulties in foreign language learning as experienced by students with special educational needs who have disturbed development in their native language.